Boosting catalytic performance for CO2 cycloaddition under mild condition via amine grafting on MIL-101-SO3H catalyst - Nguyen, Que Thi; Na, Jongbeom; Lee, Yu-Ri; Baek, Kyung-Youl (Elsevier BV, 2024)
The efforts to achieve sustainable chemical conversion and efficient CO2 utilization are critical to addressing climate change and environmental sustainability, and therefore the development of effective CO2 conversion catalysts is crucial. In this study, novel acid-base bifunctional catalysts, MIL-101-SO3H@Atz and MIL-101-SO3H@DAtz, were successfully synthesized using MIL-101-SO3H as an acid support material through post-synthetic modification with 3-amino-1,2,4-triazole (Atz) and 3,5-diamino-1,2,4-triazole (DAtz) for CO2 conversion reaction. The incorporation of the amine species into MIL-101-SO3H created unique synergistic effects with dual acid-base catalytic sites, facilitating the efficient conversion of CO2 and epoxides into cyclic carbonates. Among the catalysts, MIL-101- SO3H@DAtz demonstrated superior catalytic performance with achieving 100% epichlorohydrin (ECH) conversion with over 99% selectivity to cyclic carbonate with high selectivity of > 99% under the ambient condition of 1 bar CO2 without any co-catalyst or solvent. The elucidated CO2 cycloaddition reaction mechanism highlights the synergistic effects of acid-base functionalities and CO2-philic Lewis bases as well as hydrogen bonding donor groups, providing valuable insights into the factors contributing to superior catalytic performance. The simulated flue gas (15% CO2/85% N-2, v/v) was also conducted using MIL-101-SO3H@DAtz catalyst. Additionally, the MIL-101-SO3H@DAtz catalyst exhibited remarkably robust structural stability and recyclability, maintaining its activity over multiple cycles.